Relationship between intellectual capital and performance of small and medium manufacturing enterprises in Kenya - Muturi Moses Murimi; Beatrice Elesani Ombaka; Joseph Muchiri (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: The purpose of the Study was to establish the relationship between intellectual capital and performance of small and medium manufacturing enterprises in Kenya. Design/methodology/approach: The study adopted positivist philosophy. The research designs were descriptive survey as well as explanatory research design. The target population consisted of all the small and medium manufacturing enterprises in Kenya with a sample of 183 respondents comprising of one respondent from each firm, being either the Managing director, General Manager, Production Manager or Strategic Manager. Data analysis was conducted using descriptive statistics and inferential analysis. Findings: The study concluded that intellectual capital had no significant influence on performance of small and medium in Kenya and therefore investment in intellectual capital should be economically justified. Research limitations/implications: The data used in the study was collected for a period of ten years only and the results may not be used to make long term inference regarding the relationship that exist between the study variables. Originality/value: The findings of this study significantly contribute to the existing pool of knowledge regarding the concept of intellectual capital and its implications on organizational performance. Scholars and other researchers would find the outcomes of this study relevant as reference material to advance in their research.
Keywords: M12; M10; M13; 330; Intellectual capital; Performance; Small and Medium Manufacturing Enterprises